Performance, blood parameters, and carcass yield of broiler chickens supplemented with Mexican oregano oil - Méndez Zamora, Gerardo; Durán Meléndez, Lorenzo Antonio; Hume, Michael E.; Silva Vázquez, Ramón (2017)
ABSTRACT - The objective of the current study was to evaluate performance, blood parameters, and carcass yield of broilers supplemented with Mexican oregano oil. A total of 162 one-day-old broilers were randomly distributed into three dietary treatments: control diet (without oregano oil or antibiotic); control diet + 0.25 g kg–1 of oxytetracycline; and control diet + 0.4 g kg–1 of Mexican oregano oil. Treatment with organ oil had positive effects on body weight at 35 and 42 days. Feed intake was signiﬁcantly different at 21 and at 1-42 days; control treatment presented the highest feed intake at 28 and 35 days, while treatment with oxytetracycline had the lowest feed intake from 21 to 42 days. Weekly body weight gain was different at 42 days, in which treatment with oregano oil was the highest and control the lowest. Feed efﬁciency rate was signiﬁcantly different at 42 and at 1-42 days; treatment with oxytetracycline and treatment with oregano oil had the best values over control treatment. Blood parameters were found different among treatments, in which treatment with oregano oil was the highest in cholesterol and high-density lipoprotein at 42 days. Carcass and blood biometric variables were not different among treatments. The amount of 0.4 g kg–1 of Mexican oregano oil in diets improves high-density lipoprotein, body weight, and feed efﬁciency rate of broiler chickens. Key Words: blood proﬁle, broilers, Mexican oregano